Atmospheric Plasma Spraying for Copper Coating of Ceramic Solid Electrolytes for Anode-Free Solid-State Batteries with Increased Interfacial Contact - Ockel, Manuela; Borchers, Andre; Fröhlich, Jan; Petersen, Matthias; Paschen, Timo; Christiansen, Silke; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Advances in solid-state battery technology are crucial for future energy storage solutions. Atmospheric plasma spraying (APS) offers a novel approach for producing copper coatings on ceramic solid electrolytes (SE) for anode-free solid-state batteries (AFSSBs), which generally promise increased safety and energy density. This study investigates the feasibility of APS for the fabrication of Cu-based current collectors with enhanced interfacial contact at the SE and high material deposition rates in comparison to physical or chemical vapor deposition of Cu. The qualitative results suggest that APS can produce Cu coatings with high interfacial contact without inducing high pressures through calendaring, which can lead to cracks in brittle solid electrolytes. This research addresses critical challenges in the production of AFSSBs with APS and evaluates the importance of tailored interface properties for optimized contact areas. The pressure induced by the accelerated particles is substantially lower compared to conventional calendaring tools. Surface characteristics of SE and coating were analyzed via laser scanning. SEM analysis showed several defects during splat formation, which reduces interfacial contact.<br